2009
DOI: 10.1007/s11664-009-0863-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lanthanum Additions on the Microstructure and Microhardness of Sn-3.5Ag Solder

Abstract: This study evaluates the effects of different amounts of lanthanum (La) additions on the microstructure and microhardness of Sn-3.5Ag solders. Sn-3.5Ag-xLa ternary solders were prepared by adding 0 wt.% to 1.0 wt.% La to Sn-3.5Ag alloy. Copper substrates were then dipped in the molten solders and these samples aged at 150°C for up to 625 h. The microstructure and microhardness of the as-solidified solder and the aged solder/copper samples were investigated. The Sn-3.5Ag-xLa solders comprised b-Sn, Ag 3 Sn, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…The average hardness of Composition 1 was 17.8 HV and that of Composition 2 was 19.4 HV. Lee and Chen (2009) reported that the addition of lanthanum to Pb-free alloys increased their hardnesses. Zulai et al (2021) discovered that doping the alloy with lanthanum, a rare earth element, increased the hardness, and this was also found in the work reported here.…”
Section: Furnace Melting Methods Sample Hardnessmentioning
confidence: 99%
“…The average hardness of Composition 1 was 17.8 HV and that of Composition 2 was 19.4 HV. Lee and Chen (2009) reported that the addition of lanthanum to Pb-free alloys increased their hardnesses. Zulai et al (2021) discovered that doping the alloy with lanthanum, a rare earth element, increased the hardness, and this was also found in the work reported here.…”
Section: Furnace Melting Methods Sample Hardnessmentioning
confidence: 99%
“…In a previous study [9], it was shown that the refined microstructure and large number of LaSn 3 compounds in La-containing solders give rise to a hardening effect in the as-cast state. In this study, the relationship between the hardness and the adhesive strength of the solder joint is further explored.…”
Section: Adhesive Strength and Fracture Behavior Of Sn-35ag-xla Soldmentioning
confidence: 96%
“…It was also shown that tiny amounts of RE addition yielded no more than a small improvement in the ultimate tensile strength, but increased the elongation under tensile testing by up to 30%. Many researchers have shown that the addition of RE elements to solder systems results in a refinement of the microstructure [5][6][7][8][9]. In addition, it has been shown that RE addition suppresses the growth of the intermetallic compound (IMC) layer in solder joints, thereby improving the mechanical strength [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Li and Shi (2006) and Wang et al (2011) reported that the addition of a particular amount of Bi in a Sn-Ag-Cu solder alloy could refine the grain size of the IMC and inhibit excessive IMC growth at the interface. Additionally, some studies (Wu et al, 2004;Lu et al, 2007;Dong et al, 2008;Lee and Chen 2009) on the use of rare earth elements (RE) in the solder indicated that RE doping of the solder alloy reduced the IMC layer thickness and the interdiffusion rate of interfacial reaction in a ball grid array package.…”
Section: Introductionmentioning
confidence: 99%